Effects of ramadan fasting on self esteem, cigarette and alcohol use in college students - Çalıyurt, Okan; Molla, Sebahat; Vardar, Erdal; Abay, Ercan (Journal of Dependence, 2005)
Objective: Fasting during Ramadan is a religious duty for Muslims. Muslims do not eat, drink, smoke, and have sex from dawn to sunset. Many positive or negative medical and psychological effects of Ramadan fasting have been reported. These benefits and adverse effects of Ramadan fasting to the general health of an individual may impact on self-esteem or mood state. Effects of Ramadan fasting on cigarette and alcohol use is studied in college students. Self esteem was also evaluated to show possible association between self esteem and Ramadan fasting or self esttem and alcohol use or smoking in Ramadan. Methods: In this study we investigated the effects of fasting during Ramadan on cigarette and alcohol use in 198 college students. Possible effects of self-esteem on cigarette or alcohol use and effects of regular abstinence of smoking or alcohol on self-esteem during Ramadan were also evaluated. Results: It was observed that cigarette smoking amongst male and female students was reduced during the month of Ramadan. Cigarette smoking showed to have negative effects on self-esteem of fasting subjects. There was no association between self-esteem and fasting in month of Ramadan. Conclusions: This study demonstrates Ramadan fasting could effect smoking behavior of the fasting students and self esteem is negatively effected by cigarette smoking. These results show the importance of the evaluating of the fasting behavior during the month of Ramadan in dependent patients.